Ketepatan Waktu Pelaporan Keuangan: Sistem Pengendalian Internal dan Sistem Informasi Pengelolaan Keuangan Daerah - Alwina Noviani; Decky Hendarsyah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2020)
Financial reports must provide information that is useful for making a decision, where relevant and reliable information is influenced by the timeliness of reporting. This study aims to determine the effect of internal control systems and information systems on regional financial management on the timeliness of partial and simultaneous financial reporting of case studies at the Bengkalis Department of Transportation. This research is descriptive quantitative in nature, while the data sources used in this study are primary data and secondary data. Data collection techniques in this study were interviews, documentation, questionnaires and literature study. The data analysis technique used was data quality test, data normality test, multiple linear regression test, hypothesis test and determination coefficient test. The results of this study are partially and simultaneously there is a significant influence between the internal control system and the regional financial management information system on the timeliness of financial reporting at the Bengkalis Department of Transportation.